Particle Therapy for Breast Cancer: Benefits and Challenges - Luo, Wanrong; Ali, Yasser F.; Liu, Chong; Wang, Yuchen; Liu, Caorui; Jin, Xiaoni; Zhou, Guangming; Liu, Ning-Ang (Frontiers in Oncology, 2021)
Hardon therapy with protons and carbon ions is widely attracting interest as a potential competitor of conventional photon radiotherapy. Exquisite dose distribution of charged particles allows for a higher local control of the tumor and lower probability of damage to nearby healthy tissues. Heavy ions have presumed biological advantages rising from its high-linear energy transfer (LET) characteristic, including greater cell killing effectiveness and reduced heterogeneity dependence of radiation response. Although, these advantages are clear and supported by data, only 18.0% of proton and carbon ion radiotherapy (CIRT) facilities in Europe were treating breast cancers. This review summarizes physical and radiobiological properties of charged particle, clinical use of particle beam for breast cancer and suggested approaches to overcome technical and financial challenges.